Study of Sloshing of Viscous Liquid in Containers Using Finite Element Method - Chaimanatsakun , Noppadol; Puttapitukporn, Tumrong (Agriculture and Natural Resources, 2015)
Severe liquid sloshing in moving partially-filled liquid containers following a sudden halt can generate enormous liquid pressure which can lead to vehicle accidents or damage to their internal structures. Many researchers have focused on studies of flow characteristics during the sloshing period using the fluid-structure interaction algorithm implemented in finite element analysis. The current research extended previous work to distinguish inviscid-flow models from viscous-flow models in simulations of liquid sloshing inside containers. Finite element models of water containers were developed consisting of containers with and without a water baffle. The water-filled capacities were set at 40, 60 and 80%. This research focused on analyses of surface waves, pressure waves and stress distribution on containers. When comparing inviscid-flow models to viscous-flow models at the same water-filled capacity, quite similar results were found in the shape of surface waves, maximum wave heights and the duration of occurrence of the peak von Mises stress. Nonetheless, inviscid-flow models had higher von Mises stress on the container surfaces than viscous-flow models. At 40% water-filled capacity, the water pressure randomly oscillated over time so that the peak water pressure could not be identified. The water baffle helped to minimize water pressures, heights of surface waves and von Mises stress on the container surfaces especially at 60 and 80% water-filled capacity.